Undifferentiated Connective Tissue Disease: A Case Report - Mustafa Ünübol, (Archives of Rheumatology, 2010)
Sir- I read with great interest the article published in the Turkish Journal of Rheumatology reported by Aydeniz et al. entitled ‘Undifferentiated Connective Tissue Disease: Case Report'[<r1>]. I want to discuss some important points of this article. In the laboratory findings, the authors did not report which method was used to examine anti-nuclear antibodies (ANA) and anti-ribonucleoprotein (RNP) or at which titration level anti-RNP positivity was seen. However, if ANA positivity is reported, it is of importance for the diagnosis to indicate the titration level at which positivity was seen and the examination method used[<r2>]. ANA functions as a screening test. If ANA screening test is positive, autoantibody test could be requested based on the clinical findings. However, if ANA is negative, is it not necessary to evaluate the specific autoantibody tests[<r3>]. It is known that only anti-Ro[<r2>,<r3>] and anti-Jo-1 tests may be positive when ANA test is negative[<r3>]. However, in this case, although ANA was negative, other specific autoantibodies (anti-dsDNA, anti-RNP) were examined. In this article, anti-RNP was examined and found as positive while ANA was negative. When anti-U1RNP is positive, ANA titrations are expected to be positive in high levels[<r3>]. Thus, in this case, how can the anti-RNP positivity be explained when ANA was negative? I want to make some comments about the treatment plan. As we know, in the treatment of Raynaud's phenomenon, calcium channel blockers such as nifedipine, diltiazem and amlodipine, which have a longer effect, may be effective, and I especially want to remind that angiotensin II type I receptor antagonist losartan may decrease the severity and the frequency of Raynaud's phenomenon[<r4>]. References 1. Aydeniz A, Altındağ Ö, Gürsoy S. Belirlenemeyen Bağ Dokusu Hastalığı: Bir Olgu Sunumu. Turk J Rheumatol 2009; 24: 56-7. 2. Keser G. Romatolojik Hastalıkların Tanısında Laboratuar Testleri. In: Eker Doğanavşargil, Gürbüz Gümüşdiş (eds) Klinik Romatoloji El Kitabı I. baskı. İzmir, Güven Kitabevi 2003; 117-35. 3. Arasıl T. Antinükleer Antikorlar. In: Arasıl T (ed) Kelley Romatoloji 7.baskı. Ankara, Güneş Kitabevi 2006; 311-31. 4. Oder G. Sistemik Skleroz (Skleroderma) ve İlişkili Hastalıklar. In: Soy M. (ed) Harrison Romatoloji. Nobel Tıp Kitabevleri 2007: 111-31. Sir- Undifferentiated connective tissue disease (UCTD) may present as autoimmune disease, but sufficient clinical and serologic evidence to make a precise diagnosis is usually absent[<r1>,<r2>]. This case described reported arthralgia (The patient came from an urban area) and Raynaud's phenomenon for a period of seven years and no response to all used drugs and preventive methods. The anti-nuclear antibody (ANA) titer was examined by using immunofluorescence microscopy (IFM-ANA) in our clinics. Although ANA is a screening test for autoimmune diseases as you stated, when we review the literature, there are some cases in which clinical outcome was discordant with ANA titer. The accuracy of the IFM-ANA screening test can be affected by substrate and fixative quality, microscopic optics, subjective interpretation of test results, and selection of reference range sera[<r3>]. There are considerable recent studies about more reliable and sensitive antibody testing techniques, which is beyond the scope of this article[<r4>,<r5>]. Thank you for your contribution about the treatment plan of the patient. Although there exists a great variety of drugs (calcium channel blockers, sympatholytic agents, prostaglandins, ACE inhibitors, angiotensin receptor blockers, thromboxane A2 inhibitors, serotonin antagonists and so on) tested in the treatment of Raynaud's phenomenon, as you also remarked fairly well, no gold standard therapy has been established yet[<r6>,<r7>]. The clinical experience and side effects of drugs should be taken into account when choosing the proper drugs for each patient. Ali Aydeniz Gaziantep Üniversitesi Tıp Fakültesi, Fiziksel Tıp ve Rehabilitasyon Anabilim Dalı, Gaziantep, Turkey Phone: +90 342 360 12 00 E-mail: aydeniz@gantep.edu.tr References 1. Mosca M, Tani C, Neri C, Baldini C, Bombardieri S. Undifferentiated connective tissue diseases (UCTD). Autoimmun Rev 2006; 6: 1-4. 2. Mosca M, Tani C, Bombardieri S. Undifferentiated connective tissue diseases (UCTD): a new frontier for rheumatology. Best Pract Res Clin Rheumatol 2007; 21: 1011-23. 3. Avaniss-Aghajani E, Berzon S, Sarkissian A. Clinical value of multiplexed bead-based immunoassays for detection of autoantibodies to nuclear antigens. Clin Vaccine Immunol 2007; 14: 505-9. 4. Kumar Y, Bhatia A, Minz RW. Antinuclear antibodies and their detection methods in diagnosis of connective tissue diseases: a journey revisited. Diagn Pathol 2009; 4: 1. 5. Hang LM, Nakamura RM. Current concepts and advances in clinical laboratory testing for autoimmune diseases. Crit Rev Clin Lab Sci 1997; 34: 275-311. 6. Bakst R, Merola JF, Franks AG Jr, Sanchez M. Raynaud's phenomenon: pathogenesis and management. J Am Acad Dermatol 2008; 59: 633-53. 7. García-Carrasco M, Jiménez-Hernández M, Escárcega RO, Mendoza-Pinto C, Pardo-Santos R, Levy R, et al. Treatment of Raynaud's phenomenon. Autoimmun Rev 2008; 8: 62-8.